Georg Simmel: Explaining what Goes on in Society Today - Helle, Horst (Simmel Studies, 2019)
In the following pages I hope to transfer my enthusiasm for the sociology of Georg Simmel to my readers. My hope is powered by something of a calling to pass on the message so central his writing and thinking that it can be condensed into one simple statement: Using his approach to culture, politics, and society translates the statement “you are wrong!” to “I see, that is how you look at it!” Thus, the blunt definition of the other person as being in error becomes an acknowledgment of a new insight. Based largely on Simmel's original writings an overall view of his approach, I try to present empowering the reader how topical his thinking is in light of some alarming social and political developments world wide in society today. This simple conversion from one view of a difference of opinion to another has an obvious potential of conflict reduction, and that is why it is “advertised” here.